UMPSA joins Signing Ceremony of Collaboration Note between MINDEF and MOHE - Saharudin, Ramli (UMPSA, 2025)
KUALA LUMPUR, 2 December 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is proud to be part of the signing ceremony of a collaboration note between the Ministry of Defence (MINDEF) and the Ministry of Higher Education (MOHE) held at Dewan Perkasa, Wisma Perwira ATM.